OUT OF DARKNESS COMES LIGHT AN ANALYSIS OF TAFSĪR FAID AL-RAHMĀN QS. AL-BAQARAH (2): 257 BY KH. SHOLEH DARAT - Salamah, Navis Daris (MUSHAF: Jurnal Tafsir Berwawasan Keindonesiaan, 2024)
Kiai Sholeh Darat’s Tafsīr Faid} al-Rahmān influenced RA. Kartini’s view of Islam, especially on the meaning of the Qur'an, which was previously considered sacred so that no one could interpret it. With Kartini’s request, Tafsīr Faid} al-Rahmān was written using the tartīb mush}afī writing system (following the order of the Mushaf al-Qur’an), using the tahlili interpretation method and the Ishāri (Sufistic) style. The formulation of the problem of this research is how the correlation between the term out of darkness comes the light, then what is the background of writing Tafsīr Faid} al-Rahmān, and why the term out of darkness comes the light is considered a kartini term. The method used is the maud}ū’ī interpretation method or thematic interpretation that explains Q.S. Al-Baqarah (2): 257 with the theme of Kartini’s popularized adage. Analysis of QS. Al-Baqarah (2): 257 produces two interpretations, the first by Kiai Sholeh Darat with his ishārī interpretation that z{ulumāt (darkness) means disbelief and al-nūr (light) is interpreted as faith for believers. Meanwhile, R.A. Kartini interpreted z{ulumāt (darkness) as ignorance and al-nūr (light) as guidance. Then the relevance between the term “out of darkness comes light” (habis gelap terbitlah terang) by Kartini with QS. Al-Baqarah (2): 257 as a representation of the initial openness of science in Javanese interpretation and also the opening of interpretations that could be understood by Javanese society at that time.